Pembuatan Video Profile SMP Negeri 3 Kota Bengkulu - Regita Cahyaning Yutisar; Hadi Purnomo; Tari Juita Sapitri; Nurul Ichsan (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
Media promotion is a means to introduce and offer a product or service or agency so that it can be easily recognized and known by the wider community. Before the existence of advanced technology as it is today, media promotion was done by word of mouth, after that came the promotional media in the form of newspapers, radio, posters, banners and many more. The development of the times and the increasingly sophisticated information technology is currently increasingly attractive promotional media including promotional media in the form of profile videos. State Junior High School 3 Bengkulu City is one of the government agencies that does not yet have the latest profile video in 2022. It is hoped that by making this profile video, it is easier for people to get and find information about SMP Negeri 3 Bengkulu City, as well as being able to make this profile video as promotional material in the years to come.